2017
DOI: 10.3390/ijgi6050127
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Building Conflicts in Map Generalization with an Improved PSO Algorithm

Abstract: Abstract:In map generalization, road symbolization and map scale reduction may create spatial conflicts between roads and neighboring buildings. To resolve these conflicts, cartographers often displace the buildings. However, because such displacement sometimes produces secondary spatial conflicts, it is necessary to solve the spatial conflicts iteratively. In this paper, we apply the immune genetic algorithm (IGA) and improved particle swarm optimization (PSO) to building displacement to solve conflicts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In the first step, the evaluation is performed by evaluating the effectiveness of the model in preserving the buildings’ characteristics in the generalization of buildings. In the second step, the accuracy of the proposed model is evaluated and compared with one of the recent optimization models for resolving spatial conflicts (improved PSO [IPSO], conducted by Huang et al., 2017).…”
Section: Results and Evaluationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first step, the evaluation is performed by evaluating the effectiveness of the model in preserving the buildings’ characteristics in the generalization of buildings. In the second step, the accuracy of the proposed model is evaluated and compared with one of the recent optimization models for resolving spatial conflicts (improved PSO [IPSO], conducted by Huang et al., 2017).…”
Section: Results and Evaluationsmentioning
confidence: 99%
“…In addition, the results of comparing the proposed model for resolving spatial conflicts with IPSO indicated that although the search space of the IGA is more compatible with discrete spaces and IPSO works properly in continuous spaces [which the result of study conducted by Huang et al. 2017 confirms], when combining the proposed area reduction model with the IGA with improved objective function in a continuous search space, the IGA shows a better performance than IPSO.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…During map generalization, proximity conflicts or symbol overlaps often occur between adjacent buildings or between buildings and other adjacent objects (e.g., roads) because of map scale reduction or symbol exaggeration (Liu et al, 2014). To remove these conflicts, several generalization operators have been employed, such as contextual selection (Wang, Guo, Liu, et al, 2017), aggregation (Ai & Zhang, 2007; Li et al, 2004; Shen et al, 2019), displacement (Ai et al, 2015; Bader, 2001; Bader et al, 2005; Basaraner, 2011; Bobrich, 2001; Burghardt & Meier, 1997; Fei, 2004; Harrie, 1999, 2003; Harrie & Sarjakosk, 2002; Højholt, 2000; Huang et al, 2017; Li et al, 2020; Lichtner, 1979; Liu et al, 2014; Lonergan & Jones, 2001; Mackaness, 1994; Mackaness & Purves, 2001; Peng et al, 1995; Pilehforooshha, et al, 2021; Ruas, 1998; Sahbaz & Basaraner, 2021; Sester, 2005; Sun, Guo, Liu, Lv, et al, 2016; Sun, Guo, Liu, Ma, et al, 2016; Wang, Guo, Wei, et al, 2017; Ware & Jones, 1998; Ware et al, 2002, 2003; Wei, He, et al, 2018; Wilson et al, 2003), and typification (Mao et al, 2012; Regnauld, 2001; Shen et al, 2016; Yan et al, 2021). Among these operators, displacement may be the most frequently used one in a map production environment (Ai et al, 2015; Foerster & Stoter, 2008).…”
Section: Introductionmentioning
confidence: 99%